The Effect of Severe Intraventricular Hemorrhage on the Biorhythms of Feeding in Premature Infants - Gewolb, Ira H.; Sobowale, Babatunde T.; Vice, Frank L.; Patwardhan, Abhijit; Solomonia, Nino; Reynolds, Eric W. (Frontiers in Pediatrics, 2021)
ABSTRACT: BACKGROUND: Suck-swallow rhythmicity and the integration of breathing into infant feeding are developmentally regulated. Neurological injury and breathing abnormalities can both impact feeding in preterm infants. OBJECTIVE: To determine the effects of neurologic injury independent of effects of disordered breathing on feeding biorhythms in premature infants. METHODS: Low-risk preterm infants (LRP), infants with Grade 3-4 Intraventricular Hemorrhage (IVH), those with bronchopulmonary dysplasia (BPD), and those with both BPD and IVH (BPD+IVH) were identified. 47 infants, 32-42 weeks Postmenstrual Age (PMA) were evaluated on one or more occasions (131 studies). Of these, 39 infants (81 studies) were performed at >35 weeks PMA. Coefficient of variation (COV) (=standard deviation of the inter-event (e.g., suck-suck, swallow-breath, etc.) interval divided by the mean of the interval) was used to quantify rhythmic stability. RESULTS: To adjust for PMA, only those infants >35-42 weeks were compared. Suck-suck COV was significantly lower (more rhythmically stable) in the LRP group (COV=0.274±0.051 (S.D.) compared to all other groups (BPD=0.325±0.066; IVH=0.342±0.072; BPD+IVH=0.314±0.069; all p<0.05). Similarly, suck-swallow COV was significantly lower in LRP babies (0.360±0.066) compared to the BPD group (0.475±0.113) and the IVH cohort (0.428±0.075) (p<0.05). The BPD+IVH group (0.424±0.109), while higher, was not quite statistically significant. CONCLUSIONS: Severe IVH negatively impacts suck-suck and suck-swallow rhythms. The independent effect of neurological injury in the form of IVH on feeding rhythms suggests that quantitative analysis of feeding may reflect and predict neurological sequelae.